Experimental validation of candidate schizophrenia gene CALN1 as a target for microRNA-137. (18th August 2015) - Xia, Shihui; Zhou, Xinyao; Wang, Teng; Zhang, Qiang; Li, Qiaoli; Liu, Yun; Xing, Qinghe; Wang, Lei; He, Lin; Zhao, Xinzhi
Highlights: Computational prediction of CALN1 as a target of hsa-miR-137. miR-137 down regulated the native expression of CALN1 . miR-137 inhibited CALN1 expression by binding to its 3′UTR. Abstract: MIR137, which encodes microRNA-137 (miR-137), and several of its target genes exhibit genome-wide significant associations with schizophrenia. In a previous study, we analyzed the SNPs in a group of predicted MIR137 target genes and detected genome-wide significant association of schizophrenia with rs2944829 in the CALN1 gene. However, no experimental evidence for CALN1 and MIR137 interaction has yet been reported. In this study, we first computationally analyzed the putative miR-137 target site on CALN1 and predicted that miR-137 binds CALN1 at nucleotide (nt) position 236–242 in the 3′UTR. Then we assayed gene expression by transfecting miR-137 mimics into HEK293 and SH-SY5Y cell lines. Quantitative real-time RT-PCR results showed that the expression level of CALN1 significantly decreased in cells co-transfected with miR-137 mimics compared to cells transfected with the blank control ( P  = .0046 in HEK293 cell lines, P  = .038 in SH-SY5Y cells lines). Finally, we co-transfected different combinations of miRNA mimics and either wild type CALN1 3′UTR or mutant 3′UTR reporters into HEK293 and SH-SY5Y cell lines and assessed the specificity of miRNA binding using a luciferase reporter assay. The transfection of miR-137 mimics corresponded with a considerable reduction of luciferase activity on vectors carrying the target fragment ( P  = 1.17 × 10 −5, 68% reduction in HEK293 cell line, and P  = 5.09 × 10 −6, 32% reduction in SH-SY5Y cell line). This inhibition was impaired by site-directed mutagenesis of the miR-137 target fragment. Our results provide strong evidence that CALN1 is a target of miR-137.